Prevalence of Upper Respiratory Tract Infection in Cats at Satwagia Intensive Care Bogor - Henny Endah Anggraeni; Regina Primayani; Karunia Nihaya (Journal of Applied Veterinary Science and Technology)
Background: Upper respiratory tract infections (URTI) are significant disorders affecting the respiratory system, including the sinuses, pharynx, trachea, bronchi, bronchioles, and lungs. Despite the clinical significance of URTI in feline populations, research on their prevalence in cats within Indonesia remains limited and underreported, highlighting the need for more comprehensive studies in this area. Purpose:  This study aims to determine the prevalence of upper respiratory tract infections (URTI) in cats at Satwagia Intensive Care Bogor over a one-year period (August 2022 to August 2023). Method: Data for this study were collected from veterinary examinations of patients with confirmed URTI, sourced from the medical records of affected cats over the specified one-year period. A total of 124 confirmed cases of URTI were recorded. The data were analyzed descriptively, with results presented in tables, and compared against existing literature. Quantitative analysis included prevalence calculations, followed by ANOVA to assess the relationship between various subgroups, such as breed, gender, age, and monthly incidence and the occurrence of URTI. Results:  The prevalence of URTI in cats at Satwagia Intensive Care Bogor was found to be 23.98%. Domestic breeds showed the highest prevalence at 58%, with male cats accounting for 66% of the cases. Kittens demonstrated the highest prevalence at 66%, with ANOVA revealing significant age-related differences in URTI incidence. The highest monthly prevalence was observed in November, at 12%. Conclusion: Significant age-related differences and a peak in November suggest seasonal and demographic factors. This study provides important baseline data for feline URTI in Indonesia and emphasizes the need for targeted prevention and further research.